ANALISIS PRAKTEK DUKUN SANTET : DUGAAN PELANGGARAN HAM MENURUT PRESPEKTIF HUKUM POSITIF DAN HUKUM ISLAM - Eliana, Siska (jurnal.unprimdn.ac.id, 2023)
Indonesia is a state of law that upholds justice for the community without exception. In the formulation of Pancasila, it has been stated that justice must be upheld for all Indonesian people, as well as mentioned in the Koran that being fair must be upheld; even the Koran states that the protection of life, maintenance of life, and provision of life must be given to all humans. Unrest over the protection of human rights which is sometimes violated and taken lightly by individuals who have spiritual knowledge, with different backgrounds of humans who believe and claim and consider themselves to have spiritual knowledge so that they can pose a threat to other humans who can cause accidents, make a disability and even take someone's life. This research was conducted using the search library method by retrieving data through the data collection method of writing, recording, and analyzing data. In order to provide its legal force to deal with matters related to chastity that cause criminalization, the Criminal Code Bill only focuses on prevention but not on eradication, in contrast to Islamic law, which regulates the law in chastity which regulates the details and characteristics of a person who can be punished if proven to have done things related to chastity.